Platforms and the Challenges for Workers’ Digital Action: The Brazilian Experience during the COVID-19 Pandemic - Santana, Marco (Relations industrielles / Industrial Relations, 2023)
AbstractIn this article, I will analyze the ways in which Brazilian workers are using social media to organize and mobilize. Although analysis of social media use has made great progress, in the case of worker movements it still needs further development. I will focus on the experience of Brazilian app-based delivery workers during the COVID-19 pandemic. Despite their dispersion across the country, delivery workers were able to carry out two national strikes through intense use of WhatsApp, Facebook, YouTube and Twitter. Using qualitative analysis of posts from worker organizations on social media, it was possible to identify the challenges faced by these movements when using digital media. Social media helped solve some organizational and communication problems, while producing others that workers had to deal with.SummaryIn this article, I will analyze the ways in which Brazilian workers are using social media to organize and mobilize. I will focus on the experience of Brazilian app-based delivery workers during the COVID-19 pandemic. My research was carried out throughout July 2020, when the workers went on strike for higher pay and better working conditions. I employed a qualitative methodology of observing, selecting and analyzing about five hundred social media posts by delivery workers and their unions, associations and independent collectives. To organize the strike, they most often used Facebook, YouTube, WhatsApp, Twitter and Instagram. I thus focused on these platforms while collecting text, audio and video posts. I also obtained empirical data through monitoring and direct observation of the movement in the streets, as well as through interviews with delivery workers. The results indicate that the movement succeeded in expanding and disseminating its influence among and beyond delivery workers through the complementary use of online and offline actions. The movement thus gained more visibility and was better able to organize spatially dispersed workers. Engagement and participation were ensured through the use of networks, which thus played a prominent role in helping build and disseminate a collective identity, and which then became a means to undertake political action. Despite their gains, delivery workers also encountered formidable challenges. Their greater visibility increased the ability of companies to identify and repress movement organizers. In addition, internal fragmentation was not overcome, either offline or online. Although these movements owe their strength to social media, digital organization alone cannot solve their political or organizational problems.